2013
DOI: 10.1177/1557988312474034
|View full text |Cite
|
Sign up to set email alerts
|

Energy Drink Use and Its Relationship to Masculinity, Jock Identity, and Fraternity Membership Among Men

Abstract: The present study examined whether previous findings linking masculinity constructs and health behaviors applied to a relatively recent health risk behavior for men, the consumption of energy drinks. In addition, it also examined whether self-identifying as a jock and being a member of a fraternity would moderate the relationships between masculinity constructs and energy drink consumption. A total of 589 men completed measures of three masculinity constructs (endorsement of traditional masculinity ideology, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
1
18
0
2
Order By: Relevance
“…The present results revealed that energy drink consumption was significantly higher among males compared to females. This finding agrees with results of many other studies [10,11,18,19,22]. A reason that can be given for the higher intake of energy drinks among males may be because Saudi females are less practicing physical activity than males and energy drinks are mostly marketed for increasing physical performance [8].…”
Section: Discussionsupporting
confidence: 92%
“…The present results revealed that energy drink consumption was significantly higher among males compared to females. This finding agrees with results of many other studies [10,11,18,19,22]. A reason that can be given for the higher intake of energy drinks among males may be because Saudi females are less practicing physical activity than males and energy drinks are mostly marketed for increasing physical performance [8].…”
Section: Discussionsupporting
confidence: 92%
“…In the USA, Wimer and Levant [17] surveyed 589 adult men 19-63 years of age to consider the relationships of masculinity, athlete identity, and fraternity membership to energy drink consumption. Almost half of those surveyed (48%) consumed energy drinks; most (40%) limited their use to one drink per day.…”
Section: Motivation For Usementioning
confidence: 99%
“…Miller (2008) also found that energy drink use was positively associated with the modified CMNI, and that the modified CMNI mediated the relationship between jock identity and energy drink consumption. Wimer and Levant (2013) found that age, endorsement of traditional masculinity ideology, and conforming to the masculine norms of risk taking and primacy of work were significant predictors of energy drink consumption among a sample of students and community men. Furthermore, jock identity moderated the relationship between the endorsement of traditional masculinity ideology and energy drink consumption whereas fraternity membership moderated the relationship between conforming to the masculine norm of violence and energy drink consumption.…”
mentioning
confidence: 92%